Gendered threads: Policy barriers to sustainable textiles lifecycles - Ferrero-Regis, Tiziana; Pushpamali, Chamari N. N. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This research into global and Australian policy in textile circularity focusses on Queensland as a case study. Queensland is still lacking a comprehensive roadmap to textile circularity and does not have a strategy for used clothing collection. These activities are left to charities, which benefit from tax breaks, and industry, which is heavily subsidized with public money, ignoring the reality of an industry that is made of micro and small businesses and is predominantly female. Policies that are not scrutinized through a gender lens could continue to create gender disparities, inequalities and systemic barriers, leaving behind women who want to enter the formal repair economy.